PEMANFAATAN APLIKASI LINKTREE DALAM PEMBELAJARAN BAHASA INDONESIA TEKS LAPORAN HASIL OBSERVASI DI KELAS X MPLB SMK NEGERI 7 MEDAN - Hasibuan, Mutiara Sany; Fahmy Dalimunthe, Syairal; Surip, M.; Prihasti Wuriyani, Elly (Jurnal Bahastra, 2024)
This study aims to examine the utilization of Linktree application in learning Indonesian Language Observation Report Text in class X MPLB SMK Negeri 7 Medan. The research method used is a case study with the research subjects of class X MPLB students. The research was conducted by observing the use of Linktree in facilitating access to information and learning materials. The results showed that the utilization of Linktree application can improve the efficiency and effectiveness of learning for students of class X MPLB SMK Negeri 7 Medan. With Linktree, students can easily access various sources of information, references, and links related to lessons provided by the teacher. In addition, the use of Linktree also makes it easier for students to organize and manage learning materials in a structured manner. In the growing context of distance learning, the utilization of Linktree application makes a positive contribution in facilitating the learning process of X MPLB students of SMK Negeri 7 Medan. However, an in-depth understanding of how to use Linktree optimally is needed so that its benefits can be optimized in the context of learning for X MPLB students of SMK Negeri 7 Medan. This research is expected to provide new insights into the application of technology in education and provide recommendations for further development.